Fabricating votes for Putin: new tests of fraud and electoral manipulations from Russia - Skovoroda, Rodion; Lankina, Tomila (Taylor & Francis, 2016)
We extend the “fraud forensics” research to systematically explain precinct-level and regional variations in electoral manipulations in Russia’s March 2012 presidential election. Parametric last-digit frequency tests (a multivariate extension of last-digit tests) are employed to analyze fraud heterogeneity during the vote count stage. We also utilize author-assembled data harvested from the election monitoring non-governmental organization Golos’s regional reports of misconduct to explore the co-variance of last-digit fraud with other irregularities extending beyond the falsification of electoral records. We find that while higher regional education levels positively correlate with exposure of electoral malpractice, an educated populace may also incentivize regional officials to channel misconduct toward election-day fraud – perhaps because pre-electoral manipulations would be more visible to the public than tampering with ballots, and thus, more vulnerable to exposure. Furthermore, last-digit fraud is associated with (a) fake turnout counts; (b) fake votes disproportionally benefitting Putin; and (c) vote “re-distribution” whereby votes cast for some candidates are systematically miscounted. We also find that citizen reports of election-day misconduct are positively correlated with our region-specific last-digit fraud measures. The results indicate that reports by independent observers of sub-national electoral irregularities could be employed as reasonably reliable indicators of fraud, and could be utilized alongside other data to ascertain the incidence of misconduct in Russia and other settings.